2004
DOI: 10.1088/0022-3727/37/11/007
|View full text |Cite
|
Sign up to set email alerts
|

Growth of oriented films of La0.67Ca0.33MnO3and La0.67Sr0.33MnO3on SrTiO3using chemical solution deposition

Abstract: Oriented thin films of La 0.67 Sr 0.33 MnO 3 and La 0.67 Ca 0.33 MnO 3 were fabricated on a SrTiO 3 (002) single crystal substrate by the chemical solution deposition (CSD) process. The CSD grown films have electronic and magnetotransport properties which are comparable to those of films prepared by the pulsed laser technique and to those of the bulk single crystal samples. The magnetoresistance of the films was found to be very similar to those of pulsed laser deposition grown films and they show no contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 20 publications
(16 reference statements)
2
19
0
Order By: Relevance
“…The activation energy E a for the La 0.67 Ca 0.33 MnO 3 film is ≈66.04 meV. This value is comparable with literature values of the activation energies of films prepared by various methods, such as E a ≈ 60 meV for a strain-relaxed 200 nm film prepared by the pulse laser deposition (PLD) method [19], E a ≈ 97 meV for an LCMO film prepared by the chemical solution deposition (CSD) method [17] and E a ≈ 82.15 meV for an LCMO film prepared by the PLD method [20]. Our calculation is also in agreement with the results for La 1−x Na x MnO 3 films prepared by the CSD method [15].…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The activation energy E a for the La 0.67 Ca 0.33 MnO 3 film is ≈66.04 meV. This value is comparable with literature values of the activation energies of films prepared by various methods, such as E a ≈ 60 meV for a strain-relaxed 200 nm film prepared by the pulse laser deposition (PLD) method [19], E a ≈ 97 meV for an LCMO film prepared by the chemical solution deposition (CSD) method [17] and E a ≈ 82.15 meV for an LCMO film prepared by the PLD method [20]. Our calculation is also in agreement with the results for La 1−x Na x MnO 3 films prepared by the CSD method [15].…”
Section: Resultssupporting
confidence: 84%
“…In order to use films of manganites actively in technology, however, it is of importance to grow high-quality films that are technologically viable. In the literature, there are many studies which investigate the physical properties of manganite films [10][11][12][13][14][15][16][17][18][19][20]. As for the preparation of CMR films, there are many methods available, such as pulse laser deposition (PLD), molecular beam epitaxy (MBE), magnetron sputtering, metalorganic chemical vapour deposition and sol-gel deposition.…”
Section: Introductionmentioning
confidence: 99%
“…14), 15) In the past, LSMO thin films have been fabricated by MOD, 14)19) and it has been found that the use of STO(001) substrates enables the epitaxial growth of LSMO thin films.…”
Section: )7)mentioning
confidence: 99%
“…It is observed that the properties of these films such as resistivity, CMR, transition temperature (T C ) and magnetic properties strongly depends on preparation conditions, thickness, substrate temperature and substrate used for film deposition, etc. Among the several deposition techniques such as a sol-gel [8], spray pyrolysis method [9] and RF sputtering method [10,1,[11][12][13], etc., the pulsed laser deposition (PLD) technique is one of the widely used techniques to grow thin film of such materials. In PLD, the stoichiometry of the target is authentically reproduced in the film if the conditions during the deposition of the film are judiciously picked.…”
Section: Introductionmentioning
confidence: 99%